Associations of nine composite inflammatory indices with clinical outcomes after mechanical thrombectomy for acute ischemic stroke: a single-center retrospective study - Min Yuan; Hui He; Longyi Zheng; Yueyue Tang; Shuang Tang; Jia Duan; Wenli Xing; Ao Qian (Frontiers in Neurology, 2026)
Objective This study aims to explore the associations of nine common composite inflammatory indices with hemorrhagic transformation (HT), unfavorable outcome, and all-cause mortality in patients with acute ischemic stroke (AIS) following mechanical thrombectomy (MT). Methods A retrospective study was conducted with composite inflammatory indices, including systemic immune-inflammation index (SII), systemic inflammation response index, pan-immune-inflammation value, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio, neutrophil-to-platelet ratio, C-reactive protein-to-lymphocyte ratio, and neutrophil percentage-to-albumin ratio. Blood sampling was performed before MT procedure. Unfavorable outcome was defined as modified Rankin Scale score > 2 at 90-day follow-up. Multivariable analyses were performed to explore the associations between composite inflammatory indices and clinical outcomes with false discovery rate (FDR) correction, and the continuous indices were standardized to z-scores. The SII, NLR and PLR, all of which showed consistent significant relationships with clinical outcomes, were subjected to further subgroup analyses. Results There were 508 patients included, with age of 73 [interquartile range (IQR) 64–78], 233 (45.9%) female patients, and National Institutes of Health Stroke Scale score of 15 [IQR 12–19]. The SII, NLR and PLR, whether treated as continuous or categorical variable (classified into tertiles), were significantly associated with HT (SII: odds ratio [OR] 1.487, 95% confidence interval [CI] 1.206–1.843, p-FDR = 0.001; NLR: OR 1.592, 95% CI 1.292–1.977, p-FDR < 0.001; and PLR: OR 1.457, 95% CI 1.182–1.806, p-FDR = 0.001), unfavorable outcome (SII: OR 1.662, 95% CI 1.293–2.178, p-FDR < 0.001; NLR: OR 1.648, 95% CI 1.291–2.148, p-FDR < 0.001; and PLR: OR 1.707, 95% CI 1.319–2.267, p-FDR < 0.001) and all-cause mortality (SII: hazard ratio [HR] 1.392, 95% CI 1.218–1.591, p-FDR < 0.001; NLR: HR 1.284, 95% CI 1.111–1.484, p-FDR = 0.001; and PLR: HR 1.413, 95% CI 1.240–1.609, p-FDR < 0.001). Subgroup analyses revealed interactions of SII and NLR with mortality ( p for interaction = 0.029 and 0.004, respectively), indicating particularly robust associations in patients with cardioembolic stroke. Conclusion The SII, NLR and PLR may serve as consistent biomarkers of post-MT HT, unfavorable outcomes and all-cause mortality. Closer monitoring may be required for cardioembolic stroke patients with elevated systemic inflammatory burden.